1974
DOI: 10.1111/j.1151-2916.1974.tb11377.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Fracture Energy and Flaw Size in Glasses from Measurements of Mirror Size

Abstract: Fracture strengths (u), fracture-initiating flaw sizes, and mirror radii ( r ) , as outlined by either the mist or the hackle boundary, were measured for silicate and nonsilicate glasses (e.g. AsZ& and glassy carbon). For all glasses, ur112= constant. The average ratios of inner and outer mirror radii to flaw size were -1O:l and -13:1, respectively, for most of the glasses. Critical fracture energies calculated from either flaw or mirror size agreed very well with those obtained by double-cantilever-beam measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(70 citation statements)
references
References 12 publications
6
63
0
1
Order By: Relevance
“…For these specimens, γ WOF measured using the cross-sectional area was calculated to be 3.5 + 0.1 J/m 2 . This agrees with the fracture energy determined from traditional fracture mechanics test [γ = 3.5 J/m 2 ] (Mecholsky et al 1974). …”
Section: Resultssupporting
confidence: 75%
“…For these specimens, γ WOF measured using the cross-sectional area was calculated to be 3.5 + 0.1 J/m 2 . This agrees with the fracture energy determined from traditional fracture mechanics test [γ = 3.5 J/m 2 ] (Mecholsky et al 1974). …”
Section: Resultssupporting
confidence: 75%
“…Values for A reported for both silicate glasses fall in the range of 1.8-2.2 MPa·m ½ . 9)-11) Mecholsky et al 9),12) have demonstrated a general relation between the radius of the fracture mirror and the size, a, of the critical flaw initiating the fracture. The size ratio rm/a found valid for most silicate glasses is 10/1.…”
Section: Theorymentioning
confidence: 99%
“…These ratios are comparable to the ratios of 10/1 generally reported in literature for silicate glasses. 9) Hereby it is …”
Section: )-11)mentioning
confidence: 99%
“…The fracture surface of a failed glass fibres shows three characteristic regions: 1 the mirror zone, a smooth planar surface with a mirror-like finish; 2 the mist region, an area where small radial ridges can be seen; 3 the hackle, a region showing larger radial ridges [15J [16] [17]. The fracture surface is evident in specimens tested in air and those that have undergone stress corrosion.…”
Section: Fractography and Life Predictionmentioning
confidence: 99%